Are we presenting vocabulary items properly? the case of the CEFR-aligned Malaysian Form 4 English language textbook - Azaha, Nor Raihah; Li, Yaxiong; Nimehchisalem, Vahid; Mukundan, Jayakaran (Scientific Research Publishing, 2024)
Textbooks are the main sources for students to learn vocabulary, a vital aspect of language skills. The study aimed to evaluate how new words had been presented in the Form 4 English Language Textbook in Malaysia. A checklist by Hussin et al. (2016) and semi-structured interviews were employed to gather evaluations from four teachers regarding the subject matter. The analysis showed that the vocabulary presentation in Form 4 was useful, as evidenced by a mean of 3. Furthermore, it was observed that teachers with greater teaching experience expressed higher levels of satisfaction with the presentation of new vocabulary items, while those with less experience exhibited moderate levels of satisfaction. Findings offer insights for teachers, learners, textbook developers, and policymakers on using, developing, and modifying the vocabulary content of the book.